Key Sectors in the Economy of Saudi Arabia - Brika, Said K. M.; Adli, Brahim; Chergui, Khalil (Frontiers in Public Health, 2021)
The current paper shows the key sector for the Saudi Arabia economy, based on input-output model analyzes. They derived the analyses from a KSA economy, using 35 economic sectors. We find that four(4) leading sectors exceeded the values of the linkage coefficients with a value of 1, represented by both Chemicals and pharmaceutical products, manufacturing basic metals (S13), Transportation and storage (S24) and other business sector services (S31). According to the unbalanced growth theory, more attention paid to these sectors to be the primary engine for the rest of the sectors and growth. The results obtained are beneficial for Saudi Arabia economic policy success. By observing the different influences, it is possible to identify the policies expected to have a more significant indirect impact on other sectors in Saudi Arabia and are likely to develop a prudent economic policy. Given the economic dependence on oil, it is also substantial to be acquainted with the different sectors that are probable to have an overall effect on the economy for strategic, and operationally effective analysis can help.